Run spot run: capturing and tagging footage of a race by crowds of spectators - Flintham, Martin D.; Velt, Raphael; Wilson, Max L.; Anstead, Edward J.; Benford, Steve; Brown, Anthony; Pearce, Timothy; Price, Dominic; Sprinks, James (ACM, 2015)
There has been a massive growth in the number of people who film and upload amateur footage of events to services such as Facebook and Youtube, or even stream live to services such as LiveStream. We present an exploratory study that investigates the potential of these spectators in creating footage en masse; in this case, during a live trial at a local marathon. We deployed a prototype app, RunSpotRun, as a technology probe to see what kinds of footage spectators would produce. We present an analysis of this footage in terms of its coverage, quality, and contents, and also discuss the implications for a) spectators enjoying the race, and b) extracting the stories of individual runners throughout the race. We conclude with a discussion of the challenges that remain for deploying such technology at a larger scale.